Pengaruh Growth, Firm Size, Environmental Performance, dan Media Exposure Terhadap Carbon Emission Disclosure: Studi Kasus Pada Perusahaan High Profile yang Terdaftar di Bursa Efek Indonesia - Rizky Amalia Rosa; Mumun Maemunah; Yanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to test the effectgrowth, firm size, environmental  performance and media exposure to carbon emission disclosure. Growth measured by profit growth, firm size measured from the company's total assets, environmental performance is measured from the company's PROPER rating and media exposure is measured using a dummy variable. Carbon-intensive industries are given a score of 1 and non-carbon-intensive industries are given a score of 0. The presence of media coverage is given a score of 1 and vice versa. This research was conducted at the high profile company listed on the Indonesia Stock Exchange for the period 2020, 2021 and 2022. The research method in this study uses the hypothesis testing method with modeling Structural equation modeling(SEM) using SmartPLS software version 3.0. Based on testing in this research, it can be concluded that Growth  has a significant positive influence on Carbon Emission Dislosure, Firm Size has no significant effect on Carbon Emission Disclosure, Environmental Performance does not have a significant effect on Carbon Emission Disclosure, and Media Exposure significant positive effect onCarbon Emission Disclosure.